2005
DOI: 10.1021/jo0520487
|View full text |Cite
|
Sign up to set email alerts
|

Colorimetric “Naked Eye” Sensing of Anions in Aqueous Solution

Abstract: [structure: see text] The synthesis and UV-vis and NMR spectroscopic studies of thiourea-based colorimetric sensors for anions are presented. These sensors can recognize anions through hydrogen binding even in competitive pH-buffered aqueous solutions, giving rise to large color changes that are clearly visible to the naked eye.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
153
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 378 publications
(160 citation statements)
references
References 18 publications
6
153
1
Order By: Relevance
“…, and AcO À in aqueous organic media. 46 Ashokkumar et al 47 recently reported a structurally simple hydrogenbond receptor, 97, (Figure 32) that allowed selective binding and optical sensing of fluoride in an organic aqueous media with 50% water content. Compound 97 contains an amidothiourea anion-binding motif attached to BODIPY dye as a spectroscopic reporter.…”
Section: Sensingmentioning
confidence: 99%
“…, and AcO À in aqueous organic media. 46 Ashokkumar et al 47 recently reported a structurally simple hydrogenbond receptor, 97, (Figure 32) that allowed selective binding and optical sensing of fluoride in an organic aqueous media with 50% water content. Compound 97 contains an amidothiourea anion-binding motif attached to BODIPY dye as a spectroscopic reporter.…”
Section: Sensingmentioning
confidence: 99%
“…It has been demonstrated, however, that highly electron-deficient neutral hydrogen-bond donors could bind strongly hydrophilic monovalent anions such as H 2 PO 4 À , F À , and AcO À in aqueous organic media. 46 Ashokkumar et al 47 recently reported a structurally simple hydrogenbond receptor, 97, (Figure 32 By immobilizing a calix [4]arene-based anion receptor 98 ( Figure 32) onto the surface of a nanochannel in a polyimide membrane, Nie et al 48 developed a highly selective F À -sensing nanodevice functioning in aqueous solutions. Upon binding of F À to 98 via three NH hydrogen bonds, the ionic conductance through the 98-modified nanochannel at negative voltage increased.…”
Section: Sensingmentioning
confidence: 99%
“…12,13 In designing chemosensors with sensitive to the fluoride anion, its chemical features should be taken into account, in particular its small size and high electronegativity; these make it possible to envisage chemosensors allowing strong hydrogen bonding (HB) to the fluoride anion. 14 This specific interaction has become one of those most used to signal fluoride in solution due to the availability of HB donors and its strong and selective connections with anions. [14][15][16][17] In addition, the signaling unit responsible for this interaction must be responsible for the detection of the analyte using the usual spectroscopic techniques, such as UV-Vis absorption or fluorescence emission, or even naked-eye detection, the latter presenting advantages over spectroscopic techniques.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17] In addition, the signaling unit responsible for this interaction must be responsible for the detection of the analyte using the usual spectroscopic techniques, such as UV-Vis absorption or fluorescence emission, or even naked-eye detection, the latter presenting advantages over spectroscopic techniques. [14][15][16][17] According to this particular chemical interaction, different chemosensors involving urea or thiourea groups, [18][19][20] amides, 7 porphyrin 15 and phenols 6,16,17,21 have been described in the literature.…”
Section: Introductionmentioning
confidence: 99%